Good Agreement Between Echocardiography and Impedance Cardiography in the Assessment of Left Ventricular Performance in Hypertensive Patients - Leão, R (2021)
Background: Impedance cardiography (ICG) is a noninvasive hemodynamic monitoring tool which can define hypertensive patients' hemodynamic profiles and help to tailor antihypertensive therapy. This study assesses the concordance between ICG-derived indexes used to evaluate left ventricular performance and transthoracic echocardiography (TTE) in hypertensive patients. Methods: In this IMPEDDANS post-hoc analysis, the ICG-derived indexes are compared with TTE by Bland-Altman method. Statistical significance of the relationship between the values obtained was assessed by generalized linear mixed-effects models. Results: In supine position, Bland-Altman analysis showed good concordance for cardiac output (CO) (mean difference of 0.006 mL/min [-0.120; 0.133]), cardiac index (CI) (mean difference of 0.016 mL/min/m2 [-0.471; 0.504]), pre-ejection period (PEP) (mean difference of -0.216 ms [-4.510; 4.077]), left ventricular ejection time (LVET) (mean difference of -0.140 ms [-6.573; 6.293]), and systolic time ratio (STR) (mean difference of -0.00004 [-0.008; 0.008]). In orthostatic position, good concordance was found for CO (mean difference 0.028 mL/min [-2.036; 1.980]), CI (mean difference -0.012 mL/min/m2 [-1.063; 1.039]), and STR (mean difference -0.101 [0.296; 0.094]). No significant difference between methods was identified by the linear mixed-effects models. Conclusion: The ICG-derived indexes CO, CI, PEP, LVET, and STR in supine position have good agreement with TTE. Therefore, ICG can be used to accurately evaluate left ventricular performance.